School choice : the moral debate - Wolfe, Alan, 1942- (Princeton University Press, 2003)
School choice has lately risen to the top of the list of potential solutions to America's educational problems, particularly for the poor and the most disadvantaged members of society. Indeed, in the last few years several states have held referendums on the use of vouchers in private and parochial schools, and more recently, the Supreme Court reviewed the constitutionality of a scholarship program that uses vouchers issued to parents. While there has been much debate over the empirical and methodological aspects of school choice policies, discussions related to the effects such policies may h.